Upaya Guru Pendidikan Agama Islam dalam Implementasi Asesmen Nasional Berbasis Komputer Bidang Karakter bagi Anak Berkebutuhan Khusus di SLB PGRI Tlanakan Pamekasan - Khorida Hasna; Noer Zakiyah (Ideas Publishing, 2023)
There are difficulties in applying ANBK considering that SLB is a school for children with special needs. The aim of this research is to describe the efforts of PAI teachers in implementing ANBK in the character field, the results of implementing ANBK in the character field as well as the supporting and inhibiting factors. The method used in this research is descriptive qualitative. The results of the study show that the efforts of PAI teachers in implementing ANBK in the field of character are faith and belief, diversity, independence, critical thinking, creative, mutual cooperation. The result of the implementation of ANBK in the character field is that students are able to answer questions, and students can carry out worship. The inhibiting factor is the diversity of characteristics of each individual and teachers who are not graduates of PLB. While the supporting factors are the existence of student self-awareness, and teacher training.